Insécurité et sentiment d’insécurité à Bruxelles - Christophe Mincke (Brussels Studies)
Whilst security issues have once again invaded the political and media agenda these past months, with Brussels being described as a dangerous city, we are forced to recognise that very little attention has been given to the tools which allow a rational evaluation of the situation experienced by the inhabitants of Brussels. The present article consists in a partial analysis of one of these tools, namely the latest Security monitor, published in 2008. Which offences were reported most by the in-habitants of Brussels who were interviewed? What percentage of the population is affected? Do the inhabitants of Brussels feel insecure? These are some of the questions which we shall try to answer. But our answers are just a beginning, on the one hand because questions regarding insecurity and the feeling of insecurity require the utmost caution and, on the other, because the Security monitor has limitations, such as not being able to provide a precise description of the situation in Brussels in terms of insecurity. One therefore wonders why there does not appear to be a pertinent scale of analysis for Brussels as regards security issues.